Description of the obstacles faced by teachers in carrying out student attitude assessment - Purwaningsih, Kadek Dwi (Jurnal Inovasi Guru Indonesia, 2024)
Background: Student attitude assessment constitutes an essential component of holistic education, reflecting learners’ character development, social behavior, and moral values beyond academic achievement. Despite its importance, teachers frequently encounter substantial challenges in implementing attitude assessment due to its subjective and dynamic nature, as well as contextual and systemic constraints. Objective: This study aimed to describe the obstacles faced by teachers in carrying out student attitude assessment in elementary education settings. Methods: A qualitative descriptive design with a case study approach was employed. Fifteen teachers with a minimum of three years of teaching experience were selected through purposive sampling, along with school principals as key informants. Data were collected through in-depth interviews and classroom observations. The data were analyzed using thematic analysis involving data reduction, data display, and conclusion drawing. Triangulation was applied to enhance credibility and trustworthiness. Results: The findings revealed multiple interconnected obstacles. Teachers reported difficulties in ensuring objectivity and consistency due to the abstract and context-dependent nature of attitudes. Limited professional training on attitude assessment, inadequate standardized instruments, and insufficient digital literacy hindered effective implementation. Additional challenges included restricted time for systematic observation, limited technological support, and minimal parental involvement in reinforcing students’ character development. The imbalance between academic and non-academic assessment priorities further reduced the emphasis placed on attitude evaluation. Conclusion: The implementation of student attitude assessment is constrained by pedagogical, technological, institutional, and socio-cultural factors. Strengthening teacher professional development, enhancing digital literacy, improving institutional support, and fostering parent–teacher collaboration are critical to improving the effectiveness and objectivity of attitude assessment practices